Kajian Harga dan Perolehan Laba Dalam Perspektif Syariah - Suginam Suginam (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2019)
Pricing of a product in a business process is often not in accordance with the principles of fairness and honesty with business people. The big profit becomes a high motivation for business actors so that in carrying out business processes many contain fraudulent practices. To generate high profits/profits, it is not uncommon for economic actors to increase the price of products that are beyond normal limits. So that the values of faith and honesty possessed by business people are covered with the interests of one individual. In this study, the discussion focuses on the study of prices in generating profits/profits according to the Islamic view so that economic actors are expected to be able to implement sharia business processes, which are guided by honesty, justice, and pleasure by ignoring the interests of an individual.